El destierro de las ánimas : relatos del conflicto armado en las montañas olvidadas de Boyacá - Flórez Valderrama, Gerson Javier (Facultad de Ciencias de la Educación, 2024)
Eng: The exile of souls is a work that literally recreates episodes of the armed coflict that have left victims and the loss of life in the province of Lengupá, Boyacá. If the cruelty and destuction of war is unknown, literature takes a position to reveal the human condition of the survivors of this violence. Writing makes a reflection on the present that the victims live and updates the horror of their past. In these events, fiction and memory are presented as a narrative of the violence, to extract the voices and listen to the stories of the victims, stories that have remained in the dark and in silence.